2013
DOI: 10.3892/etm.2013.1103
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between inflammatory factors and post-stroke pneumonia in diabetic patients

Abstract: Pneumonia is the most common cause of mortality in stroke patients and it has been demonstrated to contribute to mortality and poor functional outcome following stroke in the majority of clinical studies. The risk of infection may be attributed to stroke-induced immunodepression syndrome (SIDS). Cytokine production is increased in SIDS. However, the correlation between biomarkers and the risk of post-stroke pneumonia in patients with diabetes mellitus is not clear. The aim of this study was to determine the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…High levels of systemic inflammatory cytokines such as IL-2, IL-6 and CRP have been demonstrated to predict future systemic infections after stroke (3,23). A similar result was also revealed in aneurysmal SAH in this study.…”
Section: █ Conclusionsupporting
confidence: 77%
“…High levels of systemic inflammatory cytokines such as IL-2, IL-6 and CRP have been demonstrated to predict future systemic infections after stroke (3,23). A similar result was also revealed in aneurysmal SAH in this study.…”
Section: █ Conclusionsupporting
confidence: 77%
“…A previous study reported that the risk of infection may be attributed to stroke-induced immunodepression syndrome (33). In our study, CAPD patients with prior stroke had higher rates of peritonitis than those without a history of stroke.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have shown that the probability of infection in patients with stroke is 21-65% [ 1 , 2 ]. Although clinical studies suggest that reduction of bulbar reflexes, drowsiness, dysphagia, and subsequent aspiration strongly increase the incidence of infections [ 1 , 3 , 4 ], recent preclinical evidence suggests that stroke-induced immunosuppression may also play a decisive role in infection risk [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%